Analisis Kebutuhan Pelatihan Pejabat Fungsional di Perwakilan Badan Kependudukan dan Keluarga Berencana Nasional Daerah Istimewa Yogyakarta - Dessy Phawestrina (Pancanaka, 2022)
Functional Officers must have the competencies needed and required according to their positions in order to perform optimally. However, there are Functional Officers who have not mastered the competence in their field of office so that it affects work performance. The gap between expectations and reality mainly occurs in the first appointed Functional Officers who have not attended basic training or competency test and Functional Officers who come from the transfer of Administrative Positions (Inpassing). Training is one of the effective ways to improve the competence. This study aims to map the competencies and training needs for Existing Functional Officers and Inpassing Functional Officers at the BKKBN DIY and provide recommendations for policy makers in an effort to empower Functional Officers. This research is quantitative with descriptive statistical data analysis. The findings obtained are that the both Functional Officers within the BKKBN DIY, have Technical, Managerial, and Social Cultural Competencies as well as competence in carrying out activities related to the fulfillment of credit scores. However, respondents feel that they still need to increase their competence through training related to their position. The required training includes Technical Training and Functional Training according to their respective Functional Positions.